Energy absorption of modified rubberized concrete block under low velocity impact loads - Abdul Kadir, Masidayu; Mokhatar, Shahrul Niza; Abd Mutalib, Nur Anis Najwa (Penerbit UTHM, 2022)
Concrete road barriers are widely used for safety by separating traffic in opposite directions. However, when subjected to impact loads such as road accidents, the road barrier can only absorb slight energy. This study intends to investigate energy absorption of modified rubberized concrete under low velocity impact loads. The design of the concrete mix containing treated and untreated crumb rubber (CR), the prediction of the modified rubberized concrete (MRC)’s penetration depth and its energy absorption was studied. The size of MRC blocks are 300 mm × 300 mm × 200 mm for seven (7) specimens, which are one (1) control (0% CR, 0%RHA), three (3) untreated CR (5% + 10% RHA, 10%+ 10% RHA, 15% + 10% RHA) and three (3) treated CR (5% + 10% RHA, 10%+ 10% RHA, 15% + 10% RHA) were design. Initially, the penetration depth was obtained from previous study and the projection of its energy absorption were then calculated using the empirical formula. From the result, it is proven that using MRC blocks with 15% treated CR is the optimum choice to be applied to produce the road barrier.